Black Sabbath and philosophy : mastering reality - Irwin, William, 1970- (Chichester, West Sussex ; Malden, MA : Wiley, 2012)
"A philosophical look at heavy metal's dark masters of reality, Black Sabbath Black Sabbath is one of the world's most influential and enduring rock bands. Dubbed "the Beatles of heavy metal" by Rolling Stone, they helped to define a genre with classic songs like "Paranoid", "Iron Man", and "War Pigs", songs whose lyrics reveal hidden depth and philosophical insight. Their songs confront existential despair, social instability, political corruption, the horrors of war, and the nature of evil. This book explores the wide range of profound ideas in the band's music and lyrics to help you understand Black Sabbath as never before"--
Includes bibliographical references and index.
Print version record.
Keywords: Black Sabbath (Musical group); Black Sabbath (Musical group); Black Sabbath (Musical group); Music and philosophy; Rock music -- History and criticism; PHILOSOPHY -- General; MUSIC -- Genres & Styles -- Rock; Music and philosophy; Rock music; Electronic books; Criticism, interpretation, etc; Electronic books